计算(x-y)(x平方+xy+y平方)-(x+y)(x平方-xy+y平方)
3个回答
=x^3-y^3-(x^3+y^3)
=-2y^3
^3表示三次方
相关问题
(X+y)y xy平方 x方+xy (x+y)平方 x平方-y平方 (x-y)平方 帮忙因式分解;...
已知x平方+xy=1,xy-y平方=-3.则x平方+y平方=( ).x平方+2xy-y平方=( ).x平方+3xy-2y
x平方-y平方=20 求((x+y)平方+4xy)((x+y)平方-4xy)
计算:【x(x平方y平方-xy)-y(x平方-x三次方y)】÷3x平方y.
(3x平方-4y平方)+[-(x平方-2xy-y平方)]-[(3x平方-2xy-y平方)]
(x平方-2xy+y平方)-2(x平方+2xy+y平方)
x平方+XY=-4,XY+Y平方=5,求X平方+2XY+Y平方
x平方+xy= - 4,xy+y平方=5,则x平方+2xy+y平方=()
若x平方+xy-2y平方=0,则(x平方+3xy+y平方)除以(x平方+y平方)=?
有这样一道题:求代数式(3x平方y+4x平方y平方-xy平方+x平方y-2x平方y平方+xy平方-4x平方y-2x平方y